Laser wakefield acceleration in tapered plasma channels — theory, simulation and experiment - Rittershofer, W (2014)
Laser-plasma accelerators are of great interest because of their ability to sustain extremely large acceleration gradients, enabling compact accelerating structures. Laser-plasma acceleration is realized by using a high-intensity short pulse laser to drive a large plasma wave or wakefield in an underdense plasma. This thesis considers the effect of axial plasma density upramps on laser wakefield acceleration. Theoretical groundwork shows that tapered plasma channels can be used to mitigate one of the main limitations of laser plasma acceleration, that is, dephasing of an electron beam with respect to the plasma wave. It is shown that it is possible to maintain an electron bunch at constant phase in the longitudinal electric fields of the laser wake field. This leads to an increased energy gain of an electron trapped in the wakefield. The required shape of the density slope is difficult to implement in experiments. Therefore, a linear density ramp is also considered which is predicted to also increase the energy gain beyond that possible in a uniform density plasma. Towards an experimental implementation it was studied how a suitable gas density profile can be established in a capillary. This was done employing simulations using the computational fluid dynamics tool kit OpenFoam and comparing these to measurements of the axial density profile based on Raman scattering. It was demonstrated that a linear density ramp could be established by applying different pressures on the capillary gas inlets. The dependence of the density profile on the capillary parameters, such as, capillary diameter and length and inlet diameter were also studied. The results of the simulations and the measurement showed excellent agreement and demonstrate that approximately linear density ramps can be generated by flowing gas along a capillary of constant cross-section Laser wakefield acceleration in plasmas with longitudinally varying density was investigated in an experiment at the Astra Laser at Rutherford Laboratories. The experiment utilised ionisation injection in order to operate in the mildly non-linear regime of laser-wakefield acceleration. The measured electron energies agree well with the theoretical predictions. It was demonstrated that an increase in the energy gain can be obtained by driving the accelerator in a ramped plasma, the electron spectrum is more narrow and the injected charge increases significantly. Measurements of the X-ray spectrum emitted by the betatron motion of the accelerated electron bunch allowed the transverse radius of the bunch to be deduced. These measurements showed that retrieved electron bunch radius is inversely proportional to the longitudinal density gradient, that is a plasma density upramp (downramp) has a decreased (increased) electron bunch radius.